Alteration of the gut microbiota after surgery in preterm infants with necrotizing enterocolitis - Lin, Huijia; Xu, Cuifang; Chen, Junjin; Ma, Xiaolu; Shi, Liping; Shi, Wei; Du, Lizhong; Ni, Yan (Frontiers in Pediatrics, 2023)
Purpose: To investigate the dynamic changes of intestinal microbiota in preterm infants with necrotizing enterocolitis (NEC) before and after treatment via a prospective case-control study. Methods: The preterm infants with NEC and preterm infants with similar age and weight (control group) were recruited in this study. They were divided into NEC_Onset (diagnosis time), NEC_Refeed (re-feed time), NEC_FullEn (full enteral nutrition time), Control_Onset, and Control_FullEn groups according to time of the fecal collected. Except basic clinical information, fecal specimens of the infants were obtained as well at indicated times for 16S rRNA gene sequencing. All of the infants were followed up after discharge from NICU and the growth data of corrected age 12 months were acquired from electronic outpatient system and telephone interview. Results: Total 13 infants with NEC and 15 control infants were enrolled. The gut microbiota analysis showed that the Shannon and Simpson index were lower in the NEC_FullEn group comparing to the Control_FullEn group (p<0.05). Methylobacterium, Clostridium_butyricum and Acidobacteria were more abundant in the infants with NEC at the diagnostic time. Methylobacterium and Acidobacteria were still more plentiful in the NEC group until treatment ending. These bacteria species were significantly positive correlated with CRP and negative correlated with platelet count. The rate of growth delayed was higher in the NEC group than that in the control group (25% vs 7.1%) at 12 months corrected age, but there was no significant difference. In addition, the pathways of synthesis and degradation of ketone bodies were more active in the NEC subgroups, including both NEC_Onset group and NEC_FullEn group. The pathway of sphingolipid metabolism was more active in the Control_FullEn group. Conclusion: Even reaching to the full enteral nutrition period, the alpha diversity in the infants with NEC who underwent surgery was still lower than that in the control infants. It may take more time to reestablish the normal gut flora for the infants with NEC after surgery. The pathways of the ketone bodies’ synthesis and degradation and the sphingolipid metabolism might be related to the pathogenesis of the NEC and growth development after NEC occurred.